Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Hydraulic Fracture Propagation in Pre-structured Media: Stress Field and Fracture Network Topology - Adrian V. Garcia; Rached M. Rached; Carlos D. Rodriguez-Hernandez; J. Carlos Santamarina (Rock Mechanics and Rock Engineering, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Assessment of microplastic retention efficiency using pilot-scale filtration systems applied to drinking water - K. Herrera; A. Egea-Corbacho; D. Coello; J. Quiroga; E. Marin; V. Monsalvo; E. Lucero; R. Rodriguez (Journal of Hazardous Materials, 2025)

Evaluating the combined methods of live planting and seed dispersal in restoration of Zostera marina (eelgrass) in Barnegat Bay, New Jersey by genetic diversity and pedigree analysis of restored populations - Nicole Rodriguez Ortiz; Nathan Cruz; Tiffany V. Santos; Paul A.X. Bologna; James J. Campanella (Aquatic Botany, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

Disease prevalence in confiscated exotic and indiginous birds and reptiles housed in a cites-authorized rescue center in Spain - M. Jimenez Martinez; A. Martin; A. Rabanal Soto; V. Hidalgo Martinez; A. Rodriguez Luis; M. Aranda Vazquez; J. De Andres Gamazo (Journal of Comparative Pathology, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Soil salinity effects on inter-plant signalling in wild cotton are contingent on herbivore load and differentially shape direct and indirect defences - Jonathan Interian-Aguiñaga; Uriel Solís-Rodriguez; Yeyson Briones-May; Patricia Guadarrama-Chávez; Marine Mamin; Mary V. Clancy; Ted C. J. Turlings; Xoaquín Moreira; Luis Abdala-Roberts (Planta, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Exploring Nutritional Condition of Merluccius hubbsi During Early Life Stages: Environmental Drivers and Possible Implications on Subsequent Recruitment - Julieta Rodriguez; Nadia M. Alves; Harold Fenco Chavesta; Gustavo J. Macchi; Agustin Schiariti; Rosana Di Mauro; Marina V. Diaz (Fisheries Oceanography, 2025)
The early life stages of fish represent a period of high energy requirements due to profound changes that characterize the passage to adulthood, crucial for fisheries recruitment. This study focuses on the North Patagonian Frontal System (NPFS) that guarantees successful larval development and fulfills the three postulates of Bakun's “fundamental triad” in regards to nutrients, concentration of food, and retention of eggs and larvae inside the favorable area. The objective was to evaluate the nutritional condition of Merluccius hubbsi larvae and juveniles, from the Patagonian stock in January during austral summer (2010–2021). The standardized RNA/DNA index (RDs) was used. Interannual variation in the larval condition was observed in relation to NPFS features. RDs were positively linked to the stratification of the water column in the stratified zone. An opposite trend was observed between larval condition and potential egg production that might indicate the existence of density‐dependent mechanisms. On the other hand, the positive relation between larval condition and egg production of older females (≥7 years) supports the idea of a maternal effect on larval survival. There was also a positive relationship between juveniles condition, body size, and recruitment, but no relationship was observed with the stratification of the water column. The high sensitivity of the RDs index links physiological state with survival probability, informing on factors affecting eggs, larvae, and juveniles until their posterior recruitment. This study identified the stratified area of the NPFS as a favorable nursery zone, providing crucial information for managing populations under high fishing pressure.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Feed intake, preferences, in vivo digestibility, and nutritional value of tedera (B. bituminosa var. bituminosa) and maralfalfa (Pennisetum purpureum) in Canary sheep - M. Barbera; V. Mendoza-Grimón; J. Espinosa; E. Rodriguez-Ponce; A. Gracia; E. SanJuán; M. R. Ventura (Tropical Animal Health and Production, 2025)
This study evaluated the nutritional value and energy content of tedera ( B. bituminosa var. bituminosa ) and maralfalfa ( Pennisetum purpureum ) through analyses of chemical composition, digestibility, intake, and preference trials. Tedera was compared with maralfalfa and alfalfa hay ( Medicago sativa ). Tedera showed higher crude protein (193 g CP/kg DM) and estimated energy (10.5 MJ DE/kg DM) but lower dry matter (286.3 g DM/kg) and neutral detergent fiber (373 g NDF/kg DM) than both maralfalfa and alfalfa hay. The in vitro organic matter digestibility (IVOMD) of tedera was 61.7%, compared to 51.0% for alfalfa hay and 66.3% for maralfalfa. Digestible organic matter (DOM) ranged from 467 g/kg DM in alfalfa hay to 566.4 g/kg DM in tedera. Four Canary sheep with a mean body weight (BW) of 42.2 ± 5.0 kg were used for digestibility and preference trials. The live weights of the sheep were recorded at the start and end of the 12-day trial. Feed offered and refusals were weighed and recorded daily for eight days, while feces were collected for four days to calculate apparent in vivo digestibility. For tedera, the apparent in vivo OM digestibility, estimated digestible energy, and digestible organic matter were 69.4%, 11.8 MJ/kg DM, and 637.7 g/kg DM, respectively. Preference and feed intake were compared between tedera, maralfalfa and alfalfa hay. Total DM consumption was 1091.3 g/day (tedera + maralfalfa + alfalfa hay), with alfalfa hay intake representing 40.8%, maralfalfa 37.3%, and tedera 21.9% of the total DM consumed. However, no significant differences were observed in the ratio of forages consumed/offered (44.8% for tedera and 51.8% for maralfalfa) or in the total grams of DM, CP, and MJ/kg of DE consumed by the sheep with both forages. The sheep adopted different feeding strategies in response to the chemical composition and nutritive value of the forages. Preferences and intake in this trial were associated with high NDF content in maralfalfa and alfalfa hay and with the high CP content in tedera rather than digestibility results. This may be due to the complementarity of the three forages and the higher CP content in tedera affecting intake. Nevertheless, tedera and marafalfa could be a good forage considering its nutritive value, digestibility, and proven growth performance in herbivores.

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Engineered separator of cellulose/ionic-liquid for the fabrication of a novel device with H-type architecture and dual function: Supercapacitor and NO2 gas sensor - L. Ojeda; A. Molina; K.P. Padmasree; A.I. Mtz-Enriquez; A. Zakhidov; V. Rodriguez-Gonzalez; J. Oliva (Chemical Engineering Journal, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

A solar evaporator fabricated from corncob waste for the desalination of seawater and removal of oil/herbicides from contaminated water - E. Valadez-Renteria; J. Oliva; A.I. Oliva; M.A. Ruiz-Gomez; A. Encinas; V. Rodriguez-Gonzalez (Chemosphere, 2024)

Effect of biosolid compost amended on Pb availability in soils cultivated with lettuce - M. E. Gómez; G. V. Ferreyroa; M. J. Salazar; M. L. Pignata; J. H. Rodriguez (International Journal of Environmental Science and Technology, 2024)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Highly efficient adsorption of furosemide drug by using a Ce0.8Sm0.15Nd0.05O2-δ compound immobilized on massively wasted single use packets - E. Valadez-Renteria; J. Oliva; K.P. Padmasree; A.I. Oliva; V. Rodriguez-Gonzalez (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Contrasting reproductive strategies between stress-tolerant and competitive coral taxa - K. G. Bonilla; J. R. Guest; M. V. Baria-Rodriguez (Coral Reefs, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Microbiome of the deep Lake Baikal, a unique oxic bathypelagic habitat - Pedro J. Cabello‐Yeves; Tamara I. Zemskaya; Alexandra S. Zakharenko; Mariya V. Sakirko; Vyacheslav G. Ivanov; Rohit Ghai; Francisco Rodriguez‐Valera (Limnology and Oceanography, 2020)
Lake Baikal is the deepest lake in the world. Its depth provides the only bathypelagic (> 1000 m deep) freshwater habitat on Earth and its oxic, ultra‐oligotrophic features make it a freshwater counterpart of the deep ocean. Here we have analyzed metagenomes from 1250 and 1350 m deep samples and built 231 metagenome‐assembled genomes (MAGs). We detected high fractions of Thaumarchaeota (ca. 20% of 16S rRNA reads) and members of the candidate phyla radiation (CPR) (3–4.5%). Among the MAGs, we obtained ammonia‐oxidizing archaea (AOA, Nitrosopumilaceae) and bacteria (AOB, Nitrosomonadaceae), and nitrite‐oxidizers (Nitrospirae) indicating very active nitrification. A new clade of freshwater SAR202 Chloroflexi and methanotrophs ( Methyloglobulus ) were also remarkably abundant, the latter reflecting a possible role of methane oxidation as well. Novel species of streamlined and cosmopolitan bacteria such as Ca. Fonsibacter or acI Actinobacteria were more abundant at the surface but also present in deep waters. Conversely, CPRs, Myxococcales, Chloroflexi, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) archaea, or Gammaproteobacteria were found only in bathypelagic samples. We noted various important taxonomic and metabolic differences between deep aphotic region of Lake Baikal and marine waters of similar depth: Betaproteobacteriales, CPR, and DPANN superphylum were only found in bathypelagic Baikal, while Deltaproteobacteria, Gammaproteobacteria, or Alphaproteobacteria prevailed in oceanic samples. The genes mediating ammonia and methane oxidation, aromatic compound degradation, or alkane/methanesulfonate monooxygenases were detected in higher numbers in deep Baikal compared to their oceanic counterparts or its own surface. Overall, depth seems to be less relevant than salinity in configuring the microbial community.

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Relationships between variability in precipitation, river levels, and beef cattle production in the Brazilian Pantanal - Ana Gabriela de J. Araujo; Guillermo O. Obregón; Gilvan Sampaio; Antonio Miguel V. Monteiro; Luiz Tadeu da Silva; Balbina Soriano; Carlos Padovani; Daniel Andres Rodriguez; Jelena Maksic; José Felipe Silva Farias (Wetlands Ecology and Management, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Thalassospira australica sp. nov. isolated from sea water - Elena P. Ivanova; Mario López-Pérez; Hayden K. Webb; Hooi Jun Ng; Thi Hoang Yen Dang; Natalia V. Zhukova; Valery V. Mikhailov; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2016)

Long‐term hurricane damage effects on tropical forest tree growth and mortality - Edmund V. J. Tanner; Francisco Rodriguez-Sanchez; John R. Healey; Robert J. Holdaway; Peter J. Bellingham (Ecology, 2014)
Hurricane winds can have large impacts on forest structure and dynamics. To date, most evaluations of hurricane impacts have focused on short‐term responses after a hurricane, often lacked pre‐hurricane measurements, and missed responses occurring over longer time scales. Here, we use a long‐term data set (1974–2009, 35 years) of tree stems (>3 cm in diameter at 1.3 m aboveground) in four sites (0.35 ha in total) in montane rain forest (∼1600 m elevation) in Jamaica to investigate the patterns of crown damage in individual stems by Hurricane Gilbert in 1988, and how subsequent growth and mortality were affected by hurricane damage, sprouting, and the incidence of multiple stems. Topographical position on a mountain ridge was the best predictor of crown damage, followed by crown size and species identity. The average diameter growth rate of stems that survived the hurricane was greater than that pre‐hurricane for the whole 21‐yr post‐hurricane period. Growth rates of stems with damaged crowns increased less than those with undamaged crowns; differences in growth rate between damaged and undamaged trees disappeared after 11 years. Hurricane‐damaged stems had two to eight times higher mortality than undamaged stems for 19 years post hurricane. Many stems sprouted shortly after the hurricane, but few sprouts managed to establish (grow to >3 cm diameter at breast height). However, sprouting and multi‐stemming were associated with reduced mortality rate, particularly in damaged trees. From an initial population of 1670 stems in 1974, 54% were still alive in 2009 (21 years after the hurricane). We conclude that despite the high frequency of hurricane damage to tree crowns and the subsequent increased mortality rate in this hurricane‐prone tropical montane forest, many stems will be hit and recover from several hurricanes in their lifetime.

Trophic ecology of Lampanyctus crocodilus on north‐west Mediterranean Sea slopes in relation to reproductive cycle and environmental variables - E. Fanelli; V. Papiol; J. E. Cartes; O. Rodriguez‐Romeu (Journal of Fish Biology, 2014)
This study examined the population structure, reproductive cycle and feeding pattern of the lanternfish Lampanyctus crocodilus in the Balearic Basin (north‐west Mediterranean Sea) from a depth of 450 to 1800 m and at a seasonal scale. Juveniles were mainly located at shallower depths, but also at deepest stations in autumn, while adults mostly inhabited intermediate depths with their centre of population density (CPD) located at 800–1000 m of depth. The migration of adults to deeper depths was detected in late summer to autumn, probably linked to the occurrence of nepheloid layers at c. 1200 m, which in turn enhances the biomass of the zooplankton prey. The diet was mainly based on euphausiids and mysids, with marked seasonal variations both on the upper (450–800 m) and lower (1000–1800 m), where suprabenthic gammariids and pelagic decapods were also dominant. Stomach fullness increased from winter to autumn on the US , while it had a maximum in spring on the LS , in parallel with high consumption of gelatinous zooplankton, which is probably more available after the phytoplankton bloom in late winter. Reproduction occurred in winter, confirmed by the higher percentage of mature females and high gonadosomatic indices ( I G ) at both depth ranges. Hepatosomatic indices ( I H ) showed an inverse trend to I G on the US, except in autumn, and was almost parallel on the LS, probably attributable to the migration of adults, which determined different temporal schemes in energy use and storage for reproduction on the US v . LS. Consistent with the different patterns observed at the two depth ranges, environmental drivers of fullness ( i.e. feeding intensity) and I G (as a proxy of reproductive cycle) differed on the US and LS. The biomass of mysids and euphausiids was the greatest explanatory variables of fullness on the US and LS, pointing to the increasing feeding intensity when a resource was more available. I H also explained fullness, suggesting that greater feeding intensity in pre‐reproductive periods enabled energy storage in the liver. I G was linked directly ( i.e. mysids) or indirectly ( i.e. surface primary production recorded 2 months before sampling) to food availability, implying a rapid response to vertical food inputs by deep‐sea predators. Also, I G in L. crocodilus was related to population density, which suggests aggregations for reproduction. Estimates of L. crocodilus trophic levels, and of other accompanying mesopelagic fishes, indicated that the species feed through a continuum spanning the third trophic level, confirming the key role of mesopelagic fishes in transferring organic carbon between trophic levels. Trophic niche segregation among mesopelagic species was pronounced and non‐overlapping groups could be distinguished because of the different vertical distribution and migratory behaviour. The study highlights the important role of the benthic boundary layer in sustaining benthopelagic communities in the deep Mediterranean Sea and the need to study the biology of a species throughout its whole depth range and not just at exploited depths ( i.e . fishing grounds).

Multiple spine boutons are formed after long-lasting LTP in the awake rat - N. I. Medvedev; G. Dallérac; V. I. Popov; J. J. Rodriguez Arellano; H. A. Davies; I. V. Kraev; V. Doyère; M. G. Stewart (Brain Structure and Function, 2014)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Family history of various cancers and pancreatic cancer mortality in a large cohort - Eric J. Jacobs; Carmen Rodriguez; Christina C. Newton; Elizabeth B. Bain; Alpa V. Patel; Heather Spencer Feigelson; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

Use of blood-pressure-lowering medication and risk of prostate cancer in the Cancer Prevention Study II Nutrition Cohort - Carmen Rodriguez; Eric J. Jacobs; Anusila Deka; Alpa V. Patel; Elizabeth B. Bain; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Proteomic analyses of monocyte-derived macrophages infected with human immunodeficiency virus type 1 primary isolates from Hispanic women with and without cognitive impairment - Dm Toro-Nieves; Y Rodriguez; M Plaud; P Ciborowski; F Duan; J Pérez Laspiur; V Wojna; LM Meléndez (Journal of NeuroVirology, 2009)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spectral and thermal sensing for nitrogen and water status in rainfed and irrigated wheat environments - G. J. Fitzgerald; D. Rodriguez; L. K. Christensen; R. Belford; V. O. Sadras; T. R. Clarke (Precision Agriculture, 2006)

Changing trends in etiology of bacteremia in patients with cancer - A. Safdar; G. H. Rodriguez; M. Balakrishnan; J. J. Tarrand; K. V. I. Rolston (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Toxicity of Santander Bay Sediments to the Euryhaline Freshwater Oligochaete Limnodrilus hoffmeisteri - P. Rodriguez; J. Arrate; M. Martinez-Madrid; T. B. Reynoldson; V. Schumacher; J. Viguri (Hydrobiologia, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Parity, Other Reproductive Factors, and Risk of Pancreatic Cancer Mortality in a Large Cohort of U.S. Women (United States) - Lauren R. Teras; Alpa V. Patel; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Jewish ethnicity and prostate cancer mortality in two large US cohorts - Carmen Rodriguez; Eric J. Jacobs; Alpa V. Patel; Eugenia E. Calle; Heather Spencer Feigelson; Dorna Fakhrabadi-Shokoohi; Michael J. Thun (Cancer Causes & Control, 2002)

Cross Reaction Between a Pan-Candida Genus Probe and Fusarium Spp. in a Fatal Case of Fusarium oxysporum Pneumonia - H. Rodriguez-Villalobos; M. Aoun; C. Heymans; J. De Bruyne; V. Duchateau; J. Verdebout; F. Crokaert (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Multivitamin use and colon cancer mortality in the Cancer Prevention Study II cohort (United States) - Eric J. Jacobs; Cari J. Connell; Alpa V. Patel; Ann Chao; Carmen Rodriguez; Jennifer Seymour; Marjorie L. McCullough; Eugenia E. Calle; Michael J. Thun (Cancer Causes & Control, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Prosthetic joint infection byPasteurella multocida - J. A. Maradona; V. Asensi; J. A. Carton; A. Rodriguez Guardado; J. Lizón Castellano (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1981)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1979)